2017
DOI: 10.1021/acs.analchem.6b04418
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry-Based Quantification of Cellular Au Nanoparticles

Abstract: There has been a great deal of research regarding the cellular association of nanoparticles (NPs), although there are only a few methods available yet for the quantitative measurements of cellular NPs. In this study, we propose a simple and quantitative method to estimate the cellular uptake of Au NPs into cervical cancer cells (HeLa) based on their side scattering (SSC) intensities measured by flow cytometry (FCM). We have compared SSC intensities of HeLa cells exposed to eight different types of Au NPs (40-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 32 publications
(60 reference statements)
7
51
0
Order By: Relevance
“…Apart from the differences in SSC and PI intensities, the FSC intensity of each population also displayed distinct features ( Figure 1b). FSC intensity is proportional to the size of cells, and changes in FSC intensity of treated cells in comparison to control cells reflect the swelling or shrinking of cells and may also provide us some hints about the toxicity of the treatment [16,24]. In the Ag 40 -treated sample, while the average FSC intensity of Type I cells was approximately 6 × 10 6 a.u.…”
Section: Single-cell Dose-response Analysis By Flow Cytometrymentioning
confidence: 97%
See 2 more Smart Citations
“…Apart from the differences in SSC and PI intensities, the FSC intensity of each population also displayed distinct features ( Figure 1b). FSC intensity is proportional to the size of cells, and changes in FSC intensity of treated cells in comparison to control cells reflect the swelling or shrinking of cells and may also provide us some hints about the toxicity of the treatment [16,24]. In the Ag 40 -treated sample, while the average FSC intensity of Type I cells was approximately 6 × 10 6 a.u.…”
Section: Single-cell Dose-response Analysis By Flow Cytometrymentioning
confidence: 97%
“…on average for all three populations. This is understandable because the scattering intensity is proportional to the particle size [5,16], so cells treated with Ag 80 NPs would have higher SSC intensity than those treated with Ag 40 NPs. Our previous study also reported that the agglomeration state of NPs can affect the amount of cellular NPs [5].…”
Section: Single-cell Dose-response Analysis By Flow Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports showed that the measured side scattering (SSC) intensities while using the flow cytometry method are linearly related to the cellular association of the GNPs as well as the core sizes of the GNPs. 41 In comparisons between inductively coupled plasma mass spectrometry and flow cytometry results on human cells, researchers found linear correlations between the cellular GNPs and the SSC intensities as measured by flow cytometry and used them to estimate the amounts of GNPs associated with cells. Using this validated technique, comparisons with the SSC intensities of glioma cells exposed to four different types of GNPs ( Figure S4) were performed.…”
Section: Figurementioning
confidence: 99%
“…Moreover, due to the cross-talk and autofluorescence issues of the fluorophores, it fails to estimate the number of cell-associated NPs quantitatively (Orecchioni et al 2017). Flow cytometry (FCM) is another technique that can simultaneously monitor cellular NP uptake and cellular responses by measuring the light-scattering and fluorescence-labeling intensities, respectively (Park et al 2017, Ha et al 2018). However, for those cells that have wide heterogeneity (e.g., immune cells), FCM is inadequate in providing simultaneous analyses of cell type, activation status, and elevation/depletion of secreted molecules due to its limited number of fluorescence detection channels.…”
Section: Introductionmentioning
confidence: 99%